2019
DOI: 10.35940/ijrte.d8204.118419
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Mobile Technology Adoption among Secondary School Teachers using the UTAUT2 Model

Abstract: Mobile technology (MT) is a mobile device that has become a fixture of gadget enthusiasts, and its use has proliferated around the world in recent years. The situation is becoming more and more popular in the field of education. As a teacher, they are also directly involved in the benefits of MT. Most teachers use MT for personal purposes such as accessing email, communicating through social media and browsing web pages. However, it is difficult to determine the driving force behind the use of MT to improve te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 28 publications
2
14
0
Order By: Relevance
“…Effort expectancy has a significant positive effect on behavioral intention. This is consistent with the hypothesis in the original UTAUT2 model ( Venkatesh et al, 2012 ; Omar et al, 2019 ; Kim and Lee, 2020 ). It is show that the convenience, system stability and difficulty of digital academic reading affect users’ behavioral intention.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Effort expectancy has a significant positive effect on behavioral intention. This is consistent with the hypothesis in the original UTAUT2 model ( Venkatesh et al, 2012 ; Omar et al, 2019 ; Kim and Lee, 2020 ). It is show that the convenience, system stability and difficulty of digital academic reading affect users’ behavioral intention.…”
Section: Discussionsupporting
confidence: 91%
“…Since then, effort expectancy (EE) has always been important influencing factor of behavioral intention (BI) and use behavior (USE) in the research of education and tourism ( Baptista and Oliveira, 2015 ). Scholars found that EE can influence secondary school teachers’ intentions to use mobile technology, or broader technology in the classroom ( Omar et al, 2019 ; Kim and Lee, 2020 ). But Botero et al (2019) found no effect of effort expectancy on attitude and behavioral intention in a m-learning study.…”
Section: Research Model Construction and Hypothesesmentioning
confidence: 99%
“…Past studies have had mixed results with some showing that performance expectancy is not significantly related to teachers’ behavioral intention to use mobile technology (Testa & Tawfik, 2017 ) while others show that performance expectancy is integral to teacher’s intention to use mobile VL as a teaching tool (Hu et al, 2020 ). More recently, UTAUT2 was used in a few studies globally, showing that PE significantly affects teachers’ behavioral intentions to use mobile devices and mobile technologies in the curriculum (Adov et al, 2020 ; Kim & Lee, 2020 ; Omar et al, 2019 ; Wong et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…This confirms the importance of designing useful instruction that helps to implement effective online learning based on expected performance that will affect teachers' behavioral intention to use or to continue using online learning. Omar (2019) found that performance expectancy has no positive impact on elementary school teachers to continue using online learning because teachers found it a challenge to adopt the skills and increase their motivations in using technology. Because the meaning of performance expectancy is that teachers believe using technology and online learning will enhance their job (Venkatesh et al, 2003), teachers in our study were required to use online learning to make them more confident to continue using online learning.…”
Section: Discussionmentioning
confidence: 98%
“…A number of studies have reported the reliability of the measurement scales of UTAUT. For example, Omar et al (2019) four the Cronbach's alpha of all UTAUT was > 0.9, which indicates the reliability of the scales of measurement. In this study, the instrument consists of two sections.…”
Section: Instrumentmentioning
confidence: 95%